2021
DOI: 10.1136/bjophthalmol-2021-319470
|View full text |Cite
|
Sign up to set email alerts
|

Generalisability and performance of an OCT-based deep learning classifier for community-based and hospital-based detection of gonioscopic angle closure

Abstract: PurposeTo assess the generalisability and performance of a deep learning classifier for automated detection of gonioscopic angle closure in anterior segment optical coherence tomography (AS-OCT) images.MethodsA convolutional neural network (CNN) model developed using data from the Chinese American Eye Study (CHES) was used to detect gonioscopic angle closure in AS-OCT images with reference gonioscopy grades provided by trained ophthalmologists. Independent test data were derived from the population-based CHES,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Also, a study showed the consistent performance of an OCT-based DL classifier for detecting gonioscopic angle closure among different populations. 32 Forth, we categorized the eyes based on gonioscopy and ONH evaluations. Labeling was performed primarily by 1 expert examiner, which could limit classifier generalizability due to inherent interexaminer differences in gonioscopy grading.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study showed the consistent performance of an OCT-based DL classifier for detecting gonioscopic angle closure among different populations. 32 Forth, we categorized the eyes based on gonioscopy and ONH evaluations. Labeling was performed primarily by 1 expert examiner, which could limit classifier generalizability due to inherent interexaminer differences in gonioscopy grading.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of AOD and TISA are associated with IOP and anatomical variations in PACD eyes and may predict a higher risk of PACD progression or poor angle widening after LPI. 8,15,16 In addition, automated measurements of ACW and LV could be beneficial for IOL selection: ACW is helpful in sizing anterior chamber and phakic IOLs, and there is evidence that LV could play an important role in determining effective lens position and calculating IOL power. [18][19][20][21][22][23] Our results demonstrate that rates of scleral spur detection are highly variable under realworld conditions without eyelid retraction during imaging, even among experienced graders.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,9 Quantitative OCT-based methods could complement gonioscopy, which remains the current standard for assessing the ACA despite being subjective, qualitative, variably reproducible, and weakly correlated with AS-OCT measurements of angle width. [10][11][12][13][14][15][16] In IOL selection, biometric parameters, including corneal curvature, anterior chamber depth (ACD), and lens thickness (LT), are measured using optical or ultrasound methods and factored into modern IOL calculators. 17 Anterior chamber width (ACW), also referred to as white-to-white (WTW) distance, is important for sizing anterior chamber and phakic IOLs.…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to diagnosis at a more advanced stage, early treatment initiation can both prevent irreversible vision loss and avoid expensive, invasive techniques used for later glaucoma stages, as the cost of management increases with glaucoma progression; its performance, however, still needs to be improved (327). The implementation of DL to AS-OCT is a fieldattracting attention; Li et al have very recently developed a novel 3D deep-learning-based digital gonioscopy system that identified angle closure suspects and that could be used as a screening method for primary angle closure glaucoma (371)(372)(373)(374)(375)(376).…”
Section: Artificial Intelligence and Glaucomamentioning
confidence: 99%